Pandemic preparedness and response to COVID-19 in South Asian countries. (March 2021) - Babu, Giridhara R.; Khetrapal, Sonalini; John, Daisy A.; Deepa, R.; Narayan, K.M. Venkat
Highlights: Preparedness levels against the coronavirus disease 2019 (COVID-19) pandemic were relatively poor in South Asian countries South Asian countries have lower mortality levels compared with other world countries COVID-19 has revealed the vulnerabilities of the health system as a whole Abstract: Introduction: There was a low level of pandemic preparedness in South Asia, but the region has done well in mounting an appropriate response to the coronavirus disease 2019 (COVID-19) pandemic. The rate and proportion of deaths attributed to COVID-19 are lower despite case surges similar to the rest of the world. Results: The COVID-19 pandemic has revealed the glaring vulnerabilities of the health system. In addition, the high burden of non-communicable diseases in South Asia multiplies the complexities in combating present and future health crises. The advantage offered by the younger population demographics in South Asia may not be sustained with the rising burden of non-communicable diseases and lack of priority setting for improving health systems. Conclusion: The COVID-19 pandemic has provided a window for introspection, scaling up preparedness for future pandemics, and improving the health of the population overall.